TAFSIR AS-SALAM IN THE SIGHT OF EPISTEMOLOGY: UNVEILING THE INTEGRATION OF ULUM AL-QUR'AN AND SOCIO-RELIGIOUS REALITY - Imam, Muhammad Aniq; Musyafak, Ahmad (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2025)
This article examines the epistemology of Tafsir As-Salām by Asmaji Mukhtar, with particular attention to the integration of ‘ulūm al-Qur’an and contemporary socio-religious realities. The study responds to a gap in modern Qur’anic exegesis scholarship, which has largely emphasized methodological and thematic aspects while paying insufficient attention to the epistemological foundations underpinning interpretive practices. Employing a qualitative approach based on library research, this study utilizes content analysis, critical discourse analysis, and contextual hermeneutics. The data are analyzed through thematic as well as symbolic–conceptual analysis of Tafsir As-Salām alongside classical and contemporary exegetical literature. The findings demonstrate that Tafsir As-Salām articulates an integrative epistemology of Qur’anic interpretation that dialogically and responsibly synthesizes naqli sources, ‘aqli reasoning, and empirical social realities. This tafsir not only preserves the authority of classical ‘ulūm al-Qur’an but also actualizes them in addressing contemporary issues such as pluralism, tolerance, peacebuilding, and the relationship between religion and science. Through its symbolic interpretive approach and ethical–transformative orientation, Tafsir As-Salām emerges as a model of moderate and contextually responsive Qur’anic exegesis. Theoretically, this study contributes to the development of Nusantara tafsir epistemology by proposing a normative–contextual paradigm that bridges classical tradition and the challenges of modernity.